Atypical polypoid adenomyoma with extensive morular metaplasia - Case report (Indian Journal of Case Reports, 2018)
Atypical polypoid adenomyoma (APA) is a rare and benign endometrial polypoid lesion. APA was found in a 38-year-old woman who presented with excessive vaginal bleeding. Histopathological examination of the polyp was consistent with “APA” with extensive morular metaplasia. Immunohistochemical marker CD10 was done to establish the diagnosis of morular metaplasia. Morular metaplasia is dissimilar to squamous metaplasia. It is sometimes misreported as adenosquamous carcinoma. This case illustrates the significance of morular metaplasia as a differential diagnosis.